TINJAUAN HAK CIPTA TERHADAP PENGGUNAAN DEEPFAKE TERHADAP LAGU “KOMANG” BERDASARKAN UNDANG-UNDANG NO. 28 TAHUN 2014 TENTANG HAK CIPTA: A Copyright Review on the Use of Deepfake on the Song ‘Komang’ Based on Law Number 28 of 2014 on Copyright - Magdalena Yossi Dian Madani; Aline Gratika Nugrahani (AMICUS CURIAE, 2025)
The skyrocketing development of technology has also changed the ecosystem of the domestic music industry. In mid-2023, many uploads on the TikTok application are in the form of song reconstruction efforts using software or applications to change the original sound with different input sounds. This research is intended to prove the existence of copyright infringement against Raim Laode based on Law No. 28 of 2014. This study identifies problems concerning the fulfillment of moral and economic rights of the song creator Raim Laode and the use of the song as a reconstruction medium with President Joko Widodo’s voice. Based on the findings, the use of song reconstruction through deepfake without permission harms the creator as no economic rights were shared.. This type of research is normative which is descriptive in nature and uses secondary data as supporting data using literature studies as an analytical method obtained qualitatively by drawing deductive conclusions. With the results of the research and conclusion, it was found that the action violates Articles 5 and 9 of Law Number 28 of 2014 on Copyright, both in terms of the moral and economic rights of the creator.